Desenvolvimento de um modelo de maturidade para Healthcare 4.0 - Medeiros, Eveliny Dias de (2023)
Although Industry 4.0 (I4.0) has already been adopted by different organizations, companies still need instruments to assess the progress achieved. Thus, maturity models (MMs) are useful tools for this purpose, but, for the most part, the literature points out that they are designed for manufacturing companies. Within the consulted literature, no maturity models were found for Healthcare 4.0. However, the impact of I4.0 technologies is also visible in health services and is called healthcare 4.0 (H4.0). In this way, these new technologies can provide enhanced and value-added healthcare services to patients. Given the above, this dissertation has as main objective to develop a maturity model for H4.0. Specifically, it is intended to (i) identify levels, dimensions and procedures of maturity models for Industry 4.0; (ii) analyze the particularities of the I4.0 concepts and technologies for health operations; (iii) analyze the adherence of the levels and dimensions of a maturity model for Healthcare 4.0 through the opinion of specialists and structure a model for H4.0; and (iv) apply the proposed model in public hospitals in Paraíba. Through a systematic literature review (SLR), it was possible to identify levels, dimensions and procedures used in the MMs, making it possible to build a reference framework with levels of maturity (from non-existent to advanced) and dimensions (people and culture, strategy, products/ services, processes/operations, governance, organization, security, technology and value creation) that can help in the adoption or development of new maturity models. Then, a survey was carried out to identify the main I4.0 technologies used in health services and based on the I4.0 MMs, a MM for H4.0 was proposed, which was evaluated by specialists and subsequently refined. The refined model considered five levels of maturity (0 for nonexistent and 4 for advanced). As for the dimensions of the model, they were synthesized into three dimensions as enablers for H4.0, such as: strategy, people and organization, and the technology dimension as practices for H4.0 (Telemedicine, Internet of Things (I0T), Big data, Cloud Computing, Autonomous Robots, 3D Printing, Virtual and Augmented Reality, Cyber-Physical Systems, Blockchain, Artificial Intelligence and Simulation). After refining the model, it was applied through case studies in two public hospitals in Paraíba that presented different levels of maturity. The results of the case studies show that Hospital 1 presented an Intermediate maturity level, while Hospital 2 presented a beginner maturity level. Despite this, it was found that the two hospitals have a lot to evolve with regard to H4.0. But the applicability of the model was verified by the way the results were obtained and by its adherence verified in the hospitals. This dissertation advances in the literature from the development and a maturity model for H4.0, since it was not found in an MM of I4.0 focused on hospital operations. In addition, the applied model can serve as a roadmap to identify the maturity level for H4.0, identifying strategic factors, people management, organizational aspects and H4.0 technologies, allowing a systemic view of the hospitals studied towards H4.0.